Cultural difference, inside and out. Issue 12 (December 2016) - Morling, Beth
Abstract: Cultural psychologists study the extent to which human psychological experience is shaped by our participation in sociocultural practices, meanings, and products. Cultural psychologists document cultural differences both inside the head (in the form of emotions, cognitions, or motivations) and outside the head (in the form of public behaviors, cultural products, or institutions). Because cultural psychologists argue that culture and psyche "make each other up, " it is appropriate to study cultural difference at many loci—not just the traditional psychological areas in which many of us were trained. In this article, I describe cultural psychological evidence based on its social visibility and tangible nature. One category is collected on private, intangible, inside‐the‐head activities such as emotions, values, or motives. Another category, social interactions and behavioral performances, is intangible, public, and outside the head and includes how people talk to each other and how they walk, drive, or dress. A third category contains cultural products, which are tangible, public, and outside the head; it includes texts, websites, advertising, art, and architecture. These varying loci of cultural psychology allow us to appropriately document cultural differences and also allow us to study how humans are shaped by, and participate in recreating, their cultural contexts.